AKSEPTABILITAS, UTILISASI DAN ADOPSI UPAYA PENANGGULANGAN HIV MELALUI KADER DESA PEDULI AIDS DARI PERSPEKTIF MASYARAKAT DI KOTA DENPASAR - Nopiyani, Ni Made Sri; Kurniati, Desak Putu Yuli; Indrayathi, Putu Ayu; Listryowati, Rina (ARCHIVE OF COMMUNITY HEALTH; Vol 2 No 2 (2013): Desember (2013))
Village AIDS Cadres (KDPA) Program has been conducted in Denpasar district since 2010. Despite the importance of community participation for a successful community based program, no research has been conducted to explore community perception regarding KDPA program.This research is aimed to explore community perceptions regarding acceptability, utilization, and adoption of the KDPA program from community perspective.The design used in this research is descriptive with qualitative data collection method through six focus group discussions in six villages in Denpasar. Data was analysed using thematic analysis.KDPA is well-accepted as it is perceived as an important issue to be tackled in the community. However, many opinions arise concerning who should be given the role "cadre". Lack of program introduction to the community, also high stigma and discrimination resulted in low utilization of the program. Villages with active KDPA have conducted a variety of HIV-related activities rarely carried out by the less active villages. There is Lack of community participation on HIV-related activities. Inequity of access to HIV information exists between adults and teenagers, between men and women, and between the member of traditional and non-traditional hamlets. Program adoption is hampered by the lack of commitment of village authorities and limited resources of KDPA program.The utilization and adoption of KDPA program are sub-optimal. Introduction of KDPA program to the community and provision of program resources should be improved.
Keywords: Village AIDS Cadres Program, acceptability, utilization and adoption.